The Implementation of a Problem Based Learning Model Assisted by Kahoot Media within a Lesson Study Framework to Enhance Learning Outcomes in Basic Science Concepts among Prospective Elementary School Teachers - Muslimin, Muslimin (Journal of Education and Computer Applications, 2025)
Prospective elementary school teachers often encounter difficulties in understanding the Basic Science Concepts course, particularly on topics such as Motion, Force, and Simple Machines. These challenges are influenced by students’ diverse academic backgrounds, which affect their initial conceptual understanding. This study aims to enhance students’ learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by Kahoot media within a Lesson Study framework. The research employed a Classroom Action Research (CAR) design consisting of four stages: planning, implementation, observation, and reflection. The participants were students from class C24D (22 students) and class C24E (23 students) of the Primary School Teacher Education (PGSD) Study Program, Campus V, Universitas Negeri Makassar. Data were collected through observation of learning activities and learning outcome tests. The findings revealed a steady improvement in students’ achievement, with the average score increasing from 62 (57.78% mastery) in the pre-cycle to 69 (64.44% mastery) in the first cycle, and reaching 86 (84.44% mastery) in the second cycle. Furthermore, student participation, collaboration, problem-solving ability, and engagement through Kahoot also increased, while lecturer performance was rated as very good. Therefore, the implementation of the PBL model assisted by Kahoot media effectively improved students’ understanding and learning outcomes in Basic Science Concepts